ABBREVIATION IN JAPANESE - Albert, Abraham (Universitas Pakuan, 2024)
This research “Abbreviation in Japanese”. This topic is chosen to describe the formation of abbreviations in Japanese. Another purpose is to discuss the meaning of words abbreviated in Japanese. This research used data from various sources, such as webs, pictures, and even videos made in Japan. The author used the note-taking technique to collect the data in this thesis. In order to analyze the data, the author used the distributional method. Based on the data analysis, the result obtained from this thesis is that various methods can do that abbreviation in Japanese; the meaning in words that had been abbreviated had not changed. The most common abbreviation that the author found in this thesis is “geryaku,” an abbreviation from compound words.